Civil Servants' Literacy Regarding Their Main Duties And Functions: A Study Of Functional Officials Equalized In 2020-2021 At The Governance Institute Of Home Affairs - Eskandar, Eskandar (Indonesian Journal of Librarianship, 2023)
Abstract Problem Statement: The initiative to transform administrative positions into functional roles via the equalization mechanism at the Governance Institute of Home Affairs (IPDN) during 2020-2021 has, overall, not succeeded in fostering professionalism in the performance of duties for Civil Servants (ASN). A significant challenge that has surfaced is that functional officials, as a result of equalization processes, often exhibit a deficiency in knowledge and understanding of their duties and functions. This deficiency is attributed to a lack of literacy concerning their respective functional positions. Purpose: The objective of this research is to ascertain the literacy of Functional Officials resulting from equalization processes concerning their functional roles. Method: This study is a descriptive research with a qualitative approach. The data collection techniques include interviews, literature studies, and documentation studies. The analysis of scientific literacy employs the Programme for International Student Assessment (PISA) 2018 framework according to The Organisation for Economic Co-operation and Development (OECD) as utilized by Nurhidayah (2020:11), covering the aspects of Context, Knowledge, and Competence. Result: This study reveals that concerning the context, Functional Officers resulting from equalization were not actively engaged in the process and discussions related to their role transitions. Regarding knowledge, they demonstrated an insufficient understanding and lack of knowledge regarding their roles and functions. Meanwhile, in terms of competence, these officers were found to lack the necessary skills and competencies to effectively fulfill their duties and functions. Conclusion: This research concludes that the literacy of Functional Officers resulting from equalization regarding their functional roles at IPDN during 2020-2021 is generally insufficient. It is suggested that the policy related to role transitions should consider their academic background capacities. Furthermore, there is a need for capacity-building and technical training to enhance the competencies of functional officers resulting from equalization, ensuring they can carry out their duties effectively, ultimately contributing to the achievement of organizational goals. Keywords: Literacy, Functional Positions, Equating